2012
DOI: 10.1155/2012/134132
|View full text |Cite
|
Sign up to set email alerts
|

Management Issues for Adolescents with Cystic Fibrosis

Abstract: The healthy adolescent will encounter major changes in biological and psychosocial domains. The adolescent period can be greatly affected by a chronic illness. Cystic fibrosis is a terminal illness that can significantly affect an adolescent's biological, mental and psychosocial health. This paper discusses general issues to consider when managing an adolescent with a chronic medical condition, and specifically how cystic fibrosis may impact upon puberty, body image, risk-taking behaviours, mental health, inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 83 publications
(128 reference statements)
2
68
0
Order By: Relevance
“…[59][60][61] Nonadherence to treatment remains a significant problem, particularly in the pediatric population. [62][63][64] Our study suggests that this may result from self-consciousness and striving to appear normal, engaging in risk-taking behaviors to gain a sense of control and independence, needing to "escape" the illness and exhaustion from the demands of treatment, and a sense of disempowerment. Motivating factors for treatment adherence included determination to maintain health in their hope for transplantation and the desire to take responsibility and demonstrate maturity.…”
Section: Figurementioning
confidence: 93%
“…[59][60][61] Nonadherence to treatment remains a significant problem, particularly in the pediatric population. [62][63][64] Our study suggests that this may result from self-consciousness and striving to appear normal, engaging in risk-taking behaviors to gain a sense of control and independence, needing to "escape" the illness and exhaustion from the demands of treatment, and a sense of disempowerment. Motivating factors for treatment adherence included determination to maintain health in their hope for transplantation and the desire to take responsibility and demonstrate maturity.…”
Section: Figurementioning
confidence: 93%
“…However, patients may feel that their illness is on display when they have to engage in medical regimens (e.g. taking tablets in public), and therefore some CF patients may consciously choose to be non-adherent to uphold this sense of invisibility (Withers, 2012). Bregnballe et al (2001) indicated that one of the main adherence barriers in CF is unwillingness to take medications in public.…”
Section: Fev 1 and Adherencementioning
confidence: 99%
“…[4] It is a time when more complex emotional relationships and social interactions develop, along with a greater reliance on the peer group, a less dependent relationship with parents, and increasing legal autonomy. [5] It is a turbulent time for healthy adolescents without chronic conditions, and can be especially turbulent for those with CF.…”
Section: Top Health Concernsmentioning
confidence: 99%
“…It is during adolescence that the full impact of CF on reproductive health becomes clear. [4] Pubertal development is found to be more delayed in females, which can negatively impact the adolescent's self-esteem. [4] Menarche for adolescents with CF is delayed by approximately 2 years, with weight being a critical predictor.…”
Section: Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation